Functional analysis of Barley (Hordeum vulgare L.) Cellulose synthase-like F6 promoter through transgene expression in rice (Oryza sativa L.). - Jamahari, Azreena (2020)
The knowledge of the functional aspects of the promoters are necessary prior to the application of the interested promoters to overexpress transgene in transgenic plants for gene study, improvement of quality traits and biofortification. Currently, there are lacking of characterised endosperm-specific promoters to produce strong transgene expression in the endosperm tissue of cereal plants at a specific grain development or maturation period. The Cellulose synthase-like F6(CslF6) gene is majorly responsible for the production of beta-glucan in the cereal plants, including barley, oat, wheat and rice. Beta-glucan can be found ubiquitously in the endosperm tissues of barley grains. The HvCslF6 promoter is predicted to drive strong endosperm-specific expression at mid to late grain development stage in transgenic rice, based on previous HvCslF6 gene expression studies. The present study characterised the functional length of HvCslF6 promoter and its tissue-specificity expression pattern through transgene expression in rice. The 2771 bp putative promoter of HvCslF6 gene from Sloop barley was isolated and analysed in-silico. Multiple endosperm-specific elements were identified along the promoter region, suggesting that the promoter may drive endosperm-specific expression pattern. Two transformation vectors, F6Prom1 (2771bpHvCslF6prom::GUS gene) and F6Prom3 (1257bpHvCslF6prom::GUS gene) were successfully constructed and permanently transformed into the Nipponbare rice. The HvCslF6 promoter was functional in transgenic rice as the GUS blue staining was observed in all tested body part of matureT0 plants and remained in the T1 seedlings. The promoter also drove selectively strong expression activity in the endosperm tissue and embryo of the rice grain in comparison to other plant body parts regardless of the promoter lengths. Both GUS histochemical staining and quantitative GUS activity analysis revealed that the expression of the GUS gene driven by 1257 bp HvCslF6 promoter was more potent than that of 2771 bp. The data suggested that the 1257 bp HvCslF6 promoter was sufficient to direct strong transgene expression specifically in the endosperm tissue of the transgenic rice. This verified endosperm-specific promoter will be useful to drive the expression of transgene in rice grain, including beta-glucan synthase, for generating high beta-glucan content rice in the future.